The Washback of Formative Assessment in EFL Instructions - Putra, Rama; Faridi, Abdurrachman (English Education Journal, 2021)
Assessment is a critical component in the process of teaching and learning. Without an effective assessment, it is impossible to know whether students have learned the lesson. This research aimed to investigate the washback of a formative assessment in EFL instructions. This study was a case study conducted at SMA Negeri 2 Singkep. The data were collected by using observation guidelines, questionnaires, interviews, and document analysis. This study has findings: 1) Good perception of formative assessment. It was drawn from interview questions and observation guidelines which showed that the teacher claimed to have good experience in implementing formative assessment, teacher figured out assessment importance, and teacher assumed by using supported media to address formative assessment. 2) Positive washback on EFL teaching. It was drawn from document analysis, observation, and interview which the results showed that the teacher provided good attention on the lesson plan, the teacher was successful on students’ engagement, the teacher used systematic instruction and understandable language use. 3) Positive washback on EFL learning. It was drawn from questionnaires and observation which the results showed students had good participation in doing a task, students had responsibility in learning, and students and the teacher had a kind relationship in the classroom. In conclusion, it is recommended that the teacher should understand more the formative assessment and readiness of the students. We suggested teachers provide oral and written advice or feedback that is written down on students' writing tasks or another subject.